Does Doctors' Perception Of Hospital Leadership Style And Organizational Culture Influence Their Organizational Commitment? - Güney, Salih; Katrinli, Alev; PARSEHYAN, BESTE GÖKÇE (Soc Personality Res Inc, P O Box 1539, Palmerston North 5330, New Zealand, 2014)
Our aim in this study was to determine the effect of organizational culture on the relationship between perception of leadership style and commitment to the organization by identifying firstly how Turkish doctors perceived the leadership behavior at private hospitals and then assessing the level of their organizational commitment. We developed and then tested a research model that incorporated leadership style, organizational commitment, and organizational culture. We distributed a survey to doctors working at four private hospitals in Turkey (N = 98). We found that doctors' perceptions of leadership behavior had a statistically significant, positive effect on their level of organizational commitment. We also found that organizational culture did not act as a moderator in this relationship.
Keywords: leadership style; organizational commitment; organizational culture; Turkey; doctors; Transformational Leadership; Conceptualization; Performance; Attitudes